Online tool for the discrimination of equi-distributions - Pöschel, Thorsten; Frömmel, Cornelius; Gille, Christoph (BMC Bioinformatics, 2003)
Background: For many applications one wishes to decide whether a certain set of numbers originates from an equiprobability distribution or whether they are unequally distributed. Distributions of relative frequencies may deviate significantly from the corresponding probability distributions due to finite sample effects. Hence, it is not trivial to discriminate between an equiprobability distribution and non-equally distributed probabilities when knowing only frequencies. Results: Based on analytical results we provide a software tool which allows to decide whether data correspond to an equiprobability distribution. The tool is available at http://bioinf.charite.de/ equifreq/. Conclusions: Its application is demonstrated for the distribution of point mutations in coding genes. © 2003 Pöschel et al; licensee BioMed Central Ltd.